Disentangling 'social supply' : a personal network study into the social world of cannabis use and its supply - Vlaemynck, Marieke (2016)
Research into the horizontal complexity of drug markets does not only suggest there are different types of drug markets, but also indicates that within these drug markets a wide variety of dealers or suppliers operate. The concept ‘social supply’ was developed in the 2000s to capture these ‘other’ forms of supply. ‘Socail supply’ refers to a supply that is ‘non-commercial’ and happens between ‘non-strangers’. This study aims to contribute to the theoretical debate on the conceptualisation of ‘social supply’. It thereby also aims to explore why social supply is described as social by young recreational cannabis users and their suppliers. During a computer-assisted interview, 50 young recreational cannabis users drew their personal network maps. Based on the results, a two-dimenstional conceptualisation of (social) supply is put forward. This definition shows the continued relevance of theories on group processes. Aside from these groups processes, an explanation for this particular way of defining appears to include a proces of normifciation